Implementation of Technology Utilization in Increasing Learning Motivation in Christian Religious Education for Students at SPNF SKB Sonder - Maya Imelda Sari Bokau; Valentino Reykliv Mokalu (CV. Rayyan Dwi Bharata, 2024)
The development of technology can increase student motivation in learning Christian religious education, especially in the application of learning systems that focus on the use of technology. With its implementation, PAK teachers must develop an PAK learning system based on technology, because the teacher is the pivot in every learning inside and outside the classroom. Changes and dynamics occur in the learning system, so PAK must be taught in the public space as well as within the confines of a fixed small space (classroom) which is the foundation for the essence of Christian values. The purpose of this writing is to find out how the implementation of the use of technology in increasing motivation to learn Christian religious education for students at SPNF SKB Sonder. In this study using qualitative research with an approach through interviews and literature study. The results and conclusions are first, Technology is important in the Learning Process, because educational technology motivates students to work independently where students are more motivated to return to study and work because modern technical equipment is available as a supporting facility in equipping students to understand each material. Second, the existence of technology will increase the learning motivation of students, especially PAK learning, PAK teaching is a vehicle for implementing technology in an effective manner, so that students can clearly understand what is being taught, because it is assisted with audio-visual media and packaging so that the learning model does not become bored so that students can freely learn and motivate students in improving achievements that are in the axis of knowing God's work in the Bible which is displayed through technology.